eNOS gene polymorphısms and transıtıonal cell cancer of the bladder (Annals of Medical Research, 2021)
Aim: In this case-control study, we examined the association between two types of eNOS gene polymorphisms (intron 4 a/b and Glu298Asp) and transitional cell carcinoma (TCC) of the bladder.Nitric Oxide (NO) is a free radical that plays a key role in various physiological and pathophysiological processes, particularly in the circulatory system. Endothelial Nitric Oxide Synthase (eNOS), as a member of NOS family, is the enzyme, responsible for the physiological production of nitric oxide in the endothelium. Polymorphisms of eNOS have been related to increased risk for different types of cancers. Material and Methods: A total of 64 patients with bladder TCC and 80 controls with similar epidemiological characteristics of patients group were evaluated and compared in terms of eNOS gene polymorphisms of two different types ((intron 4 a/b and Glu298Asp). Following DNA isolation from the blood samples, eNOS gene was replicated via PCR. The genomic distribution of two types of eNOS polymorphism was determined by gel electrophoresis following the process of restriction, for both groups. Results: The alleles most commonly observed in patient group were “ab” for intron 4 (OR= 1.80, 95% CI: 0.71-4.64; P=0.20) and “GT” for Glu298Asp polymorphisms (OR= 1.65, 95% CI: 0.85-3.22; P=0.14). Neither bladder cancer risk nor disease grade was associated with these polymorphisms. Conclusions: This study suggests that the intron 4 a/b and Glu298Asp eNOS gene polymorphisms are not associated with bladder cancer susceptibility. However, it is mandatory to conduct further trials with more patients to confirm these findings and to evaluate the association between bladder cancer and eNOS gene polymorphisms.
Keywords: Bladder cancer; Glu298Asp polymorphism; intron 4 a/b polymorphism; Nitric oxide synthase; Nitric oxide synthase polymorphism